Effect Of Nipa (Nypa Fruticans Wurmb.) Vinegar On The Inhibition Of Intestinal Glucose Absorption - Yasmin, Farjana (2021)
Nipa palm vinegar is a traditional vinegar widely used in Southeast Asia as a condiment and a home remedy for several ailments. Previous studies have reported the antihyperglycemic activity of aqueous extract of nipa palm vinegar. In this study, the effects of consuming nipa palm vinegar on postprandial glucose levels were scrutinized.